Rancang Bangun Sistem Monitoring Penggunaan Daya Listrik Berbasis Internet of Things - Sirojul Hadi; Andi Sofyan Anas; Lalu Ganda Rady Putra (PTE FTK UIN Ar-Raniry, 2022)
The modern lifestyle of Indonesian people has influenced the level of increasing of the electricity consumption. The wasteful use of household electricity even uncontrolled due to the lack of monitoring of the amount of power used. It does not enough to monitor power depends on the kWh meter because the electricity users cannot monitor every room which excessive in terms of electricity consumption. In this study, a monitoring tool was designed to monitor power consumption in each room. The purpose of this study is to determine the power consumption in each room. Thus, it is easier to save electrical energy. Implementation of the internet of things (IoT) used the Blynk platform. The results showed that the tools (design) have been successful in monitoring the power consumption of each IoT-based room. At load the laptop charger produces 99.61% efficiency, at load two lamps produces efficiency 98.94%, at fan load produces efficiency 99.08% and at load two lamps and laptop charger produces efficiency 99.07%. It can be concluded that the system built has very good efficiency and can make it easier to monitor power consumption in household electronic equipment.